Comparative study of soils - Meyer Jr., Richard (My University, 1905)
Introduction: All soils may be compared in two very distinct ways, one with respect to the chemical composition and the other the physical condition of the soil, the first dealing mainly with the amount and quality of plant food, while the latter deals with the texture of the soil and its relation to plant development. The physical condition of a soil is to a large extent due to the treatment it receives in the way of cultivation. And the fact that a soil is in good tilth can easily be recognized by the increased vigor of the plants grown upon that soil. A good physical condition of the soil is obtained largely by the work of the different implements of tillage and the various ways and times of the year these implements are used, and is therefore largely under the control of man. By changing the physical condition of the soil is the best and about the only way the agriculturist has of regulating and controlling the movements of water and air in the soil, two of the most important factors which aid in the upbuilding and maintaining of a soil. It has been found that different soils act differently toward the movements of water and air and it is for this reason the following comparisons are made. Since the water is held in the soil primarily by a farce known as surface tension, the object should be to have a given volume of soil contain as much of the soil grain surface as possible, and in view of the fact that the extent of this surface will vary inversely as the diameter of the soil grains it is evident why a soil with small grains should hold the most water. The total soil grain surface also varies with the amount of compacting the soil has received.
Citation: Meyer Jr., Richard. Comparative study of soils. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Water Holding Capacity; Coarse Grain; Fine Grain; Humus; Theses